Postprandial symptoms in a mixed-meal-test after bariatric surgery: clinical experience and a critical review of dumping syndrome Definition and Management - Samigullin, Azat; Weihrauch, Julia; Otto, Mirko; Rech, Andrea; Buchenberger, Sandra; Morcos, Michael; Humpert, Per Magnus (Obesity facts, 2025)
Introduction: Despite recent attempts to reach a consensus on the diagnostic criteria and treatment of dumping syndrome (DS) after bariatric surgery, many questions about the clinical applicability and significance of standardized provocation tests remain unanswered. The objective of this study was to retrospectively evaluate a mixed-meal-test (MMT) based on general nutritional recommendations after bariatric surgery and its clinical value in diagnosing DS. Methods: The MMT contained 15.5 g of protein, 10 g of fat, 20.7 g of carbohydrates, and 3.1 g of dietary fiber, totaling 241 kcal. Symptoms based on the Sigstad Score, along with blood sugar, hematocrit, pulse rate, and blood pressure, were collected as primary readouts. The analysis included 58 MMTs from 56 patients who reported postprandial symptoms indicative of DS and were referred to the clinic by surgeons or general practitioners. Results: Although all individuals reported significant symptoms at home, the MMT showed a positive symptom score (Sigstad Score ≥7) in only 16 cases (28%). Neither a heart rate increase >10 BPM nor the 3% hematocrit increase suggested as cut-offs for early DS by the consensus paper were associated with the Sigstad Score or individually reported symptoms. None of the participants had a postprandial glucose decrease below 50 mg/dL; one fell below 60 mg/dL and 14 fell below 70 mg/dL. A blood glucose decrease below 70 mg/dL was not associated with symptoms. Conclusion: The MMT showed that only a minority of patients reported classical DS symptoms under controlled conditions. Changes in hematocrit, heart rate, and blood sugar decrease below 70 mg/dL did not help to predict symptoms in the individuals studied. The data, in the context of existing evidence, suggest that provocation tests have little value in clinical practice and that DS as a clinical entity after bariatric surgery should be reevaluated. Dumping syndrome (DS) is a set of symptoms, which may occur in patients after bariatric surgery (weight loss surgery). These symptoms occur after meals and are attributed to a fast passage of food through the surgically altered stomach and intestine. The symptoms of DS include fainting, the need to lie down, shortness of breath, and dizziness. Current recommendations suggest measuring heart rate, taking laboratory measurements and comparing these to diagnostic criteria during a provocation test with a glucose solution. We have been using a so-called Mixed-Meal Test to evaluate the patients’ symptoms at our clinic. Patients would eat a meal designed according to recommendations for patients after bariatric surgery, made of curd, oats, apple sauce, and walnuts. Then, their symptoms, blood pressure, and blood samples would be collected for 180 min. We looked at the data from all 56 tests, we had performed at our clinic, and compared the measurements, which we had obtained, to the diagnostic criteria and symptoms reported. While all patients reported symptoms at home, only 28% reported typical symptoms during the test. We did not find meaningful associations between measurements taken by us and symptoms reported by patients. This study shows that many patients do not display typical symptoms under controlled conditions. At the same time, the diagnostic criteria seem to be unrelated to symptoms. It is not the first study showing discrepancies between measurements, diagnostic criteria, and symptoms. The current tests used for diagnosing DS may not be clinically useful and the whole concept of DS after bariatric surgery may need to be reevaluated.